OsbZIP47 Is an Integrator for Meristem Regulators During Rice Plant Growth and Development - Prakash, Sandhan; Rai, Rashmi; Zamzam, Mohamed; Ahmad, Owais; Peesapati, Raghavaram; Vijayraghavan, Usha (Frontiers in Plant Science, 2022)
Stem cell homeostasis by the WUSCHEL–CLAVATA (WUS-CLV) feedback loop is generally conserved across species; however, its links with other meristem regulators can be species-specific, rice being an example. We characterized role of rice OsbZIP47 in vegetative and reproductive development. The knockdown transgenics showed meristem size abnormality and defects in developmental progression. The shoot apical meristem (SAM) size in twenty-five-day OsbZIP47KD plants was increased as compared to the wild-type (WT). Inflorescence of knockdown plants showed reduced rachis length, number of primary branches and spikelets. Florets had defects in second and third whorl organs and increased organ number. OsbZIP47KD SAM and panicles had abnormal expression for CLAVATA peptide-like signaling genes: FON2-LIKE CLE PROTEIN1 (FCP1), FLORAL ORGAN NUMBER 2 (FON2), and hormone pathway genes: cytokinin (CK) ISOPENTEYLTRANSFERASE1 (OsIPT1), ISOPENTEYLTRANSFERASE 8 (OsIPT8); auxin biosynthesis OsYUCCA6, OsYUCCA7; and gibberellic acid (GA) biosynthesis genes such as GRAIN NUMBER PER PANICLE1 (GNP1/OsGA20OX1) and SHORTENED BASAL INTERNODE (SBI/OsGA2ox4). The effects on ABBERANT PANICLE ORGANIZATION1 (APO1), OsMADS16 and DROOPING LEAF relate to second and third whorl floret phenotypes in OsbZIP47KD. Protein interactions assays showed OsbZIP47 partnerships with RICE HOMEOBOX1 (OSH1), RICE FLORICULA/LEAFY (RFL) and OsMADS1 transcription factors. The meta-analysis of panicle transcriptomes in OsbZIP47KD, OsMADS1KD and RFLKD knockdown transgenics, combined with global OSH1 binding sites divulge potential targets coregulated by OsbZIP47, OsMADS1, OSH1 and RFL. Further, we demonstrate that OsbZIP47 redox status affects its DNA binding affinity to a cis element in FCP1, a target locus. Taken together, we provide insights on OsbZIP47 roles in SAM development, inflorescence branching and floret development.